Novel sparging strategies to enhance dissolved carbon dioxide stripping in industrial scale stirred tank reactors - Nickel, Nicolas; Fitschen, Jürgen; Haase, Ingrid; Kuschel, Maike; Schulz, Torsten W.; Wucherpfennig, Thomas; Schlüter, Michael (Frontiers in Chemical Engineering, 2024)
Aerated stirred tank reactors are widely used in bio-process engineering and pharmaceutical industries. To supply the organisms with oxygen and control the pH value, oxygen is transferred from air bubbles into the liquid phase and at the same time carbon dioxide is stripped from the liquid phase with the same gas bubbles. The volumetric mass transfer coefficients for oxygen and carbon dioxide are therefore of crucial importance for the design and scale-up of aerated stirred tank reactors. In this experimental work, the volumetric mass transfer coefficients for oxygen and carbon dioxide are investigated simultaneously to study their mutual influence. The mass transfer performance for oxygen and carbon dioxide is conducted in stirred tank reactors on 3 L laboratory scale, 30 L pilot scale and 15 000 L production scale. First, the influence of dissolved carbon dioxide on the oxygen mass transfer performance is investigated in a 30 L pilot scale stirred tank reactor. The results show that the volumetric mass transfer coefficient of oxygen is not affected by the concentration of dissolved carbon dioxide, but the total mass flux of oxygen decreases with increasing carbon dioxide concentration due to the decreasing partial pressure difference.With rising gassing rate and volumetric power input, both mass transfer coefficients for oxygen and carbon dioxide show the same increasing trend. While this trend can also be observed when scaling down to the 3 L laboratory scale reactor, a significantly different effect must be considered for the scale up to the 15 000 L industrial scale reactor. The limited absorption capacity for carbon dioxide of the gas bubbles during the long residence time in the industrial scale reactor is noticeable here, which is why the specific interfacial area is of negligible importance. This effect is used to develop a method for independent control of oxygen and carbon dioxide mass transfer performance on industrial scale and to increase the mass transfer performance for carbon dioxide by up to 25 %.